Turkish Adaptation of The Customer Inspiration Scale: Validity/Reliability Application (Third Sector Social Economic Review, 2025)
This study aims to translate and culturally adapt the 'Customer Inspiration Scale,' originally created in English by Böttger et al. (2017), into the Turkish language. The research followed the standardized scientific procedures for scale adaptation, with each stage described in detail under the "Method" section. The process involved translation and back-translation, expert evaluations, and both preliminary and final implementation phases, all conducted meticulously. Data were collected from a total of 999 adult participants residing in Turkey through both online and face-to-face methods (Study Group-1=12, Study Group-2=67, Study Group-3=920). The sample of the study consists of the Study Group-3, which includes 920 participants. EFA and CFA revealed that the scale consists of nine items across two dimensions (Inspired-by and Inspired-to) and possesses structural validity (χ²/df=4.668, TLI=.965, IFI/CFI=.977, NFI=.971, GFI=.975, AGFI=.851, RMR=.045, RMSEA=.063). Reliability analyses further confirmed the high internal consistency of the scale (Inspired-by:α=.827; Inspired-to:α=.858; Overall:α=.878). These findings suggest that the Turkish version of the Customer Inspiration Scale is a valid and reliable instrument based on both theoretical and statistical criteria. Given that customer inspiration can trigger purchase intentions, and considering the lack of such a tool in the domestic literature, this study fills a significant gap for researchers in marketing and consumer behavior. The study concludes with several recommendations from both academic and sectoral perspectives.
Keywords: Validity-Reliability; Customer Inspiration; Scale Adaptation; MArketing; Consumer Behaviour